2017
DOI: 10.5334/labphon.98
|View full text |Cite
|
Sign up to set email alerts
|

Thematic role predictability and planning affect word duration

Abstract: It is known that acoustic variation is influenced by the predictability of words and the information that they represent. What is unknown is whether acoustic reduction is also influenced by the referential predictability of thematic roles. We tested this question in two production experiments, where speakers heard a sentence with goal/source arguments, e.g., "Lady Mannerly [source] gave a painting to Sir Barnes [goal]," and described a picture of a subsequent action, e.g., "Sir Barnes threw it in the closet." … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Other work suggests that the semantic relatedness of words produced in succession might even impact production fluency, though the exact mechanisms are still debated (Balota, Boland, & Shields, ; Fink, Oppenheim, & Goldrick, ). Existing accounts that link aspects of speech timing to production ease (Arnold, ; Arnold, Kahn, & Pancani, ; Zerkle, Rosa, & Arnold, ) are also consistent with our perspective.…”
Section: Prosody and Performancesupporting
confidence: 87%
“…Other work suggests that the semantic relatedness of words produced in succession might even impact production fluency, though the exact mechanisms are still debated (Balota, Boland, & Shields, ; Fink, Oppenheim, & Goldrick, ). Existing accounts that link aspects of speech timing to production ease (Arnold, ; Arnold, Kahn, & Pancani, ; Zerkle, Rosa, & Arnold, ) are also consistent with our perspective.…”
Section: Prosody and Performancesupporting
confidence: 87%
“…In the experiments fromZerkle, Rosa & Arnold (2015), the stimulus picture did not appear until after the context sentence, so the duration of the context sentence is not as relevant. SeeZerkle, Rosa, & Arnold (2017) for a discussion of differences in planning across these two studies.…”
mentioning
confidence: 99%
“…That is, predictable referents may be easier to retrieve from memory, which in turn results in shorter forms to refer to predictable referents. So far, empirical studies have only shown production facilitation effects of predictable referents at the acoustic level (e.g., duration; Arnold et al, 2012;Zerkle et al, 2017), but not on the selection of a particular form of expression Zerkle & Arnold, 2016). Recently, however, Karimi (2022) has argued that a more accurate measure for predictability as a factor in speaker effort may be referential entropy, which takes into account the probability distribution over all potential referents in the context instead of just the likelihood of mentioning the target referent (see also Modi et al, 2017;Pickering & Gambi, 2018;Tily & Piantadosi, 2009).…”
Section: Discussionmentioning
confidence: 99%